Environmental Product Declaration Reporting in the Metal Sector - Maria Vastardi; Eugenia Filtikaki; George Mavraganis; Katerina Adam (Materials Proceedings, 2024)
In an increasingly globalized and sustainability-conscious market, the environmental attributes of products consist of the information of primary importance for the sustainable development of manufacturing companies. The aim of the paper is to statistically analyze the Environmental Product Declaration (EPD) reports that have resulted from Life Cycle Analysis (LCA) in the metal products industry based on two parameters: (i) the geographical scope and (ii) the category of the product. During recent years, EPDs have been developed as a tool for the carbon footprint assessment of products; however, they not yet very widely applied by metal-manufacturing companies and/or requested by key stakeholders as customers. Moreover, in the metal industry, the use of EPD reports is not yet as widespread as in other industrial segments such as plastics. The present article is based on the EPD Library of the official website of the International EPD System (Environdec) and the published EPDs of the Institut Bauen und Umwelt e.V. (IBU). Data were extracted, and the relevant information was compiled by using the available filters of the EPD and the IBU Libraries. Based on these data, the number of EPD reports issued by manufacturing companies was examined as per country of origin and product category.